Geography of Tourism in Quebec: A Too Short History - Zainub Ibrahim; Rémy Tremblay (Études Caribéennes)
This viewpoint looks at the evolution of the study of tourism geography as a discipline from its inception in the late 1950s, until current-day publications and foci. The study of tourism geography commenced with strong geographical influences: mainly environmental and economic. An analysis of the publications of the University of Quebec in Montreal’s Transat Chair in tourism is carried out resulting in highlighting of key aspects of tourism interest in the province over the past 30 years.  It is interesting to note that in the context of tourism geography in Quebec, the two original approaches, environmental and economic, are still very prominent. So much so, that an argument can be made that given the stressors of modern-day society, in particular Covid-19 and climate change, the importance of economic and environmental aspects of tourism geography in Quebec are now more important than ever, and it is likely that the future direction of tourism research relates closely to these fields.